Biological and prognostic value of ETV5 in high-grade serous ovarian cancer - Lu Zhang; Ruiting Fu; Ping Liu; Lijun Wang; Weihua Liang; Hong Zou; Wei Jia; Lin Tao (BMC, 2021)
Abstract Background ETS transcription factors are known to act as either positive or negative regulators of the expression of genes involved in various biological processes. It was reported that ETS variant transcription factor 5 (ETV5), a key member of the ETS family, mainly plays a role as an potential oncogene in various malignant tumors. However, the role and mechanism of ETV5 in high-grade serous ovarian cancer (HGSOC) have not been elucidated. Methods Quantitative real-time polymerase chain reaction (qRT-PCR) assay was used to detect ETV5 messenger ribonucleic acid (mRNA) expression in 87 HGSOC tissues and 35 normal fallopian tube tissues. Western blotting and qRT-PCR were used to detect the protein and mRNA expression of ETV5 in six ovarian cancer (OC) and human embryonic cell lines. Knockdown or overexpression of ETV5 in HGSOC cell lines, Cell Counting Kit-8, colony formation, and transwell assays were used to detect HGSOC cell proliferation, invasion, and migration capabilities. The chi-square test was used to analyze the clinicopathological characteristics of HGSOC patients. Survival analysis was performed using the Kaplan-Meier method, and the log-rank test was used to analyze the correlation between ETV5 expression and HGSOC patient prognosis. Univariate and multivariate analyses using the Cox regression model were conducted to determine the independent significance of relevant clinical covariates. Results Bioinformatic analysis demonstrated that ETV5 expression was significantly upregulated in OC (p < 0.05). qRT-PCR showed that ETV5 was significantly overexpressed in HGSOC tissues than in fallopian tube tissues (p < 0.05). qRT-PCR and western blotting assays demonstrated that ETV5 was relatively highly expressed in OC cell lines. ETV5 overexpression was positively associated with poor survival in HGSOC patients, therefore making it a high-risk factor for HGSOC progression. Furthermore, ETV5 promoted the proliferation, migration, and invasion capabilities of HGSOC cells. Conclusion ETV5 has a carcinogenic effect in HGSOC and can be used as a clinically effective biomarker to determine the prognosis of HGSOC patients.